Autobiographical memory functions of nostalgia in comparison to rumination and counterfactual thinking: similarity and uniqueness. Issue 2 (7th February 2018) - Cheung, Wing-Yee; Wildschut, Tim; Sedikides, Constantine
ABSTRACT: We compared and contrasted nostalgia with rumination and counterfactual thinking in terms of their autobiographical memory functions. Specifically, we assessed individual differences in nostalgia, rumination, and counterfactual thinking, which we then linked to self-reported functions or uses of autobiographical memory (Self-Regard, Boredom Reduction, Death Preparation, Intimacy Maintenance, Conversation, Teach/Inform, and Bitterness Revival). We tested which memory functions are shared and which are uniquely linked to nostalgia. The commonality among nostalgia, rumination, and counterfactual thinking resides in their shared positive associations with all memory functions: individuals who evinced a stronger propensity towards past-oriented thought (as manifested in nostalgia, rumination, and counterfactual thinking) reported greater overall recruitment of memories in the service of present functioning. The uniqueness of nostalgia resides in its comparatively strong positive associations with Intimacy Maintenance, Teach/Inform, and Self-Regard and weak association with Bitterness Revival. In all, nostalgia possesses a more positive functional signature than do rumination and counterfactual thinking.